2015
DOI: 10.3389/fpsyg.2015.00265
|View full text |Cite
|
Sign up to set email alerts
|

The relation between language and arithmetic in bilinguals: insights from different stages of language acquisition

Abstract: Solving arithmetic problems is a cognitive task that heavily relies on language processing. One might thus wonder whether this language-reliance leads to qualitative differences (e.g., greater difficulties, error types, etc.) in arithmetic for bilingual individuals who frequently have to solve arithmetic problems in more than one language. The present study investigated how proficiency in two languages interacts with arithmetic problem solving throughout language acquisition in adolescents and young adults. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 65 publications
6
39
0
2
Order By: Relevance
“…This advantage in LM+ compared to mother tongue was also found for simple multiplication in adult population (Salillas & Wicha, 2012). In a study with a similar population of bilingual participants (Van Rinsveld, Brunner, Landerl, Schiltz, & Ugen, 2015), we recently observed that not only complex (solutions up to 99) but even simple addition problems with one-digit addends were solved slower in LM-(i.e. French) than in LM+ (i.e.…”
Section: Discussionsupporting
confidence: 53%
“…This advantage in LM+ compared to mother tongue was also found for simple multiplication in adult population (Salillas & Wicha, 2012). In a study with a similar population of bilingual participants (Van Rinsveld, Brunner, Landerl, Schiltz, & Ugen, 2015), we recently observed that not only complex (solutions up to 99) but even simple addition problems with one-digit addends were solved slower in LM-(i.e. French) than in LM+ (i.e.…”
Section: Discussionsupporting
confidence: 53%
“…German uses a unit-ten order (e.g., “24” = four-and-twenty), whereas Italian, French, and English (for numbers higher than twenty) use a ten-unit order (e.g., “24” = twenty-four). This difference in word structure has been shown to influence arithmetic performance (e.g., Ellis & Hennelly, 1980; Göbel, Moeller, Pixner, Kaufmann & Nuerk, 2014; van Rinsveld et al, 2015). French, however, adds a second interference by making use of a base-20 structure for numbers between 70 and 99, while the other languages have a clear base-10 structure.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, German–French bilingual adolescents showed better performance when arithmetic tasks were presented in L1 (German) compared to L2 (French), even though later, in secondary education, mathematics had been taught in French. The effect was greater for complex addition problems (e.g., 56 + 32) compared to more simple addition problems (e.g., 4 + 2; van Rinsveld, Brunner, Landerl, Schiltz & Ugen, 2015). Taken together, research in the field of bilingual mathematics learning suggest that language is relevant for task performance.…”
Section: Introductionmentioning
confidence: 97%
“…In secondary school students enrolled in a bilingual program, Saalbach et al (2013) found a cognitive cost related to language switching from the instructional to the non-instructional language in arithmetic tasks. Similarly, Rinsveld et al (2015) found that adolescents and young adults were always better at solving complex mathematical tasks in their instructional language; on the other hand, their skills in solving complex calculations in the other language improved with their language proficiency. Another important aspect is the influence of language-specific number word structures in bilinguals’ arithmetic performances ( Prior et al, 2015 ; Rinsveld et al, 2015 ).…”
Section: Introductionmentioning
confidence: 88%
“…In contrast, an increasing number of studies also suggest that language abilities may play a pivotal role in the development of arithmetic skills (e.g., LeFevre et al, 2010 ; Purpura and Ganley, 2014 ). Third, the study of calculation skills in the bilingual population (e.g., Mondt et al, 2011 ; Prior et al, 2015 ; Rinsveld et al, 2015 ) has recently received increasing interest with the assumption that bilingualism, and specifically the case of language minority children, may offer a unique opportunity to disentangle the role of language skills in the development of calculation skills.…”
Section: Introductionmentioning
confidence: 99%